Analysis of Injuries in the Swiss U20 Elite Ice Hockey Season 2019/2020-A Retrospective Survey - Jonas Ruff; Jan Taeymans; Angela Blasimann; Slavko Rogan (MDPI AG, 2024)
(1) Background: In Switzerland, there is little data on injury characteristics in elite ice hockey players aged under 20 years (U20 Elite juniors). This study aimed to determine the injury rate and type of injury in Swiss U20 ice hockey players. (2) Methods: The present study was carried out in a retrospective, non-experimental design using an online questionnaire provided to the 314 elite players of the 12 Swiss U20 Elite ice hockey teams. The injury rate, rate ratios, injury location, type and severity of injury, and injury mechanism were reported. (3) Results: Seventy-three athletes from 11 teams volunteered (response rate = 24%). A total of 30 out of 45 recorded injuries led to time loss in practice and competition. Injury occurred once or twice during the 2019/2020 season. For each player, the injury rate was 0.66 per 1000 practice hours and 2.98 per 1000 competition hours (injury rate ratio = 4.5). The head/neck region was the most common injury location (45.5%). (4) Conclusions: Knowledge of injury characteristics in ice hockey is necessary for meaningful injury management and injury prevention. The results of the present study provide information on the injury rate, location, types, severity, and mechanism in elite Swiss U20 ice hockey players. Most injuries result from contact with another player. More strict sanctioning for irregular behavior and fair play can serve as preventive measures. Further studies should examine different preventive measures such as wearing full-face coverage.